Lightweight dissoluble foam aluminum alloy and preparation method thereof
By developing a soluble foam aluminum alloy containing Mg, Cu, Zr, In, Ga, Sn and Ti elements, the problems of insufficient strength and stability of existing temporary plugging agents are solved, and the demand for efficient sealing and low-cost oil and gas mining is achieved. It has the characteristics of self-dissolving, reducing environmental impact.
Patent Information
- Application Number
- CN202411903750.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-11
AI Technical Summary
The temporary plugging agents used in existing oil and gas mining have problems such as low strength, poor chemical and thermal stability, and incomplete dissolution, which are difficult to meet the needs of efficient sealing and low cost.
A new type of soluble foam aluminum alloy is adopted, with chemical components including Mg, Cu, Zr, In, Ga, Sn and Ti. By regulating the content and porosity of these elements, the characteristics of high strength, low density and controllable dissolution rate are achieved.
It achieves high-efficiency sealing in oil and gas wells, and has low density, excellent mechanical properties and controllable dissolution properties, meets the needs of temporary fracturing, and dissolves itself after completing the task, reducing environmental burden and subsequent treatment costs.
Smart Images

Figure CN119800173A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a light soluble foamed aluminum alloy and a preparation method thereof, belonging to the technical field of nonferrous metal preparation and processing. Background Art
[0002] The exploration and exploitation of unconventional oil and gas resources is related to the development pattern of world energy and is also a major demand for improving oil recovery. At present, the exploitation of unconventional oil and gas resources mainly adopts horizontal well fracturing technology. During the fracturing process, in order to achieve the fracturing effect, temporary plugging materials are needed to temporarily plug the casing perforations and remove them in time. The temporary plugging agents commonly used in the fracturing transformation of complex fracture networks in unconventional reservoirs include temporary plugging balls mainly for temporary plugging of blastholes, conventional temporary plugging agents and fiber temporary plugging agents mainly for temporary plugging of fracture channels, and other new synthetic temporary plugging agents.
[0003] In recent years, with the rapid technological progress in the research direction of soluble metals, soluble magnesium / aluminum alloy temporary plugging balls have made great progress in temporary plugging of blastholes. However, this type of material has problems such as high density, high cost, and uncontrollable dissolution rate. On the other hand, temporary plugging agents such as polymer knots are often used in unconventional oil and gas production, which have problems such as low strength, poor chemical and thermal stability, and incomplete dissolution. With the widespread application of multi-stage fracturing technology in horizontal wells in low-grade oil and gas reservoirs, there is an urgent need for temporary plugging materials with adjustable density, controllable dissolution rate, low residue, low cost and high efficiency. Therefore, in order to achieve the blocking of blastholes and fracture channels, it is necessary to develop a new generation of temporary plugging materials with low density, high compressive strength, controllable dissolution, and good chemical and thermal stability.
[0004] Dissolvable aluminum foam is a porous metal composite material composed of dissolvable solid metal (mainly aluminum alloy) and closed pores. It has a dense skin that greatly improves the material strength, so that it can withstand fracturing. At the same time, the interior is composed of a closed pore structure, and the gas occupies a considerable volume fraction. Dissolvable aluminum foam has a unique combination of properties such as low density, excellent specific weight mechanical properties and high energy absorption. The notable feature of dissolvable aluminum foam is its low and adjustable density, and the absolute density can reach 0.6g / cm 3 -1.3g / cm 3, fast dissolution speed, high porosity, generally can reach 50% to 80%. More importantly, traditional temporary plugging alloy materials can only control the dissolution rate by adjusting the alloy composition or dissolution conditions (such as temperature, pressure, solvent, etc.), while the soluble foam aluminum alloy material can not only provide the above two methods to regulate the dissolution rate, but also can regulate the dissolution rate more efficiently by regulating different porosities, that is, the volume fraction of soluble alloy entities. The advantage of low density can also make the soluble foam aluminum alloy temporary plugging agent in the fracturing fluid in different suspended states, which is more conducive to flowing with the fracturing fluid in the plugging section and realizing the temporary plugging function. This provides a new way to solve the problem for the selection of temporary plugging materials.
[0005] US 200710181224 A (publication date: August 9, 2007) discloses a composition, which includes one or more active metals in a major proportion and one or more alloying products in a minor proportion. It mainly contains metals and alloying products in Groups I and II of the periodic table, for example, functional alloys of gallium (Ga), indium (In), zinc (Zn), bismuth (Bi) and aluminum (Al). The composition is characterized in that its activity and degradation rate can be controlled under specific conditions, but because the material has strong metallic properties, the compressive strength can only reach tens of MPa. Therefore, how to effectively improve the mechanical properties while ensuring the corrosion rate is a factor that needs to be considered in the next step.
[0006] Chinese patent CN101560619A (publication date: October 21, 2009) relates to a method for preparing a degradable alloy, which includes adding one or more alloying products to an aluminum or aluminum alloy melt to obtain a soluble alloy, but does not involve mechanical properties.
[0007] Patent CN114959522A discloses an aging treatment method for high-strength sandwich structure foam aluminum material, which increases the compressive strength from 4.0MPa to 4.9MPa. The compressive strength is slightly improved, but the effect is not obvious.
[0008] CN110468313B patent discloses a high-strength closed-cell aluminum foam alloy and a preparation method thereof. The chemical composition and weight percentage of the closed-cell aluminum foam alloy are: Mg: 0.3-0.6%, Zn: 5.0-8.3%, Cu: 0.5-1.2%, Ca: 1.5-2.5%, Y: 0.05-0.10%, and the balance is Al. The compressive strength of the aluminum foam alloy prepared by this method is between 18-32MPa. This method introduces Zn, Mg, Cu, and Ca elements into the aluminum foam, which can form a large amount of eutectic network Al-Zn-Mg-Cu-Ca precipitation phase in the pore wall matrix, effectively strengthen the matrix, and improve the compressive yield strength of the foam metal, but does not mention the mechanical properties such as tensile strength.
[0009] The invention patent application with publication number CN116005046A (published on April 25, 2023) discloses a high elongation soluble aluminum alloy and a preparation method thereof. A high elongation soluble aluminum alloy of Al-Mg-Cu-Ga-In-Sn-Bi is designed and prepared. The chemical composition of the soluble aluminum alloy is: Mg 0.5-1.5%, Cu 0.1-0.5%, Ga 0.5-1.5%, In 0.5-1.2%, Sn 0.5-1.8% and Bi 0.5-1%, and the balance is Al. The alloy has a fast dissolution rate and an elongation of nearly 30%, and is suitable for processing materials such as fracturing balls and bridge plug tools in staged fracturing.
[0010] The invention patent with authorization announcement number CN114717456B (published on July 8, 2022) discloses a high-temperature soluble aluminum alloy, preparation method and use. The invention designs a soluble aluminum alloy of Al-Mg-Ga-In-Sn, whose chemical composition is: Mg 1.5%, Ga 0.1%, In 0.7%, Sn0.6%, and the balance is Al and unavoidable impurity elements. The alloy has a faster dissolution rate and an elongation of nearly 30%.
[0011] The above-mentioned related patents are concentrated in two aspects: one is the preparation of soluble aluminum alloys. The innovation is concentrated in the adjustment of the soluble alloy composition, the preparation of the soluble alloy body and the mechanical and solubility properties of the soluble alloy, but it basically focuses on rods and does not involve any foam materials; the second is the preparation of foam aluminum alloy materials, but it basically focuses on mechanical properties and does not involve research related to the solubility properties of foam aluminum alloys.
[0012] Therefore, in order to address the problems of insufficient strength and dissolution rate, and high density of temporary fracturing plugging agents used in existing oil and gas development, it is necessary to develop a new type of soluble foam aluminum alloy material that has the characteristics of high strength, high porosity and low density, while also possessing the controllable solubility and excellent mechanical properties of soluble aluminum alloys. Summary of the invention
[0013] The invention provides a novel soluble foam aluminum alloy, in particular a soluble foam aluminum alloy used for temporary plugging in shale oil and gas exploitation and a preparation method thereof.
[0014] One aspect of the present invention relates to a soluble foam aluminum alloy, characterized in that the chemical composition and weight percentage of the soluble foam aluminum alloy are: Mg: 3.0~9.0wt.%; Cu: 0.5~5.0wt.%; Zr: 0.05~1.0wt.%; In: 0.05~3wt.%; Ga: 0.5~5wt.%; Sn: 0.05~1.5wt.%; Ti: 0.05~2.0wt.%; the balance is Al.
[0015] In one implementation, the weight percentage of In+Ga+Sn in the soluble foamed aluminum alloy is between 1.4 and 7.0 wt. %, preferably between 2.7 and 6.8 wt. %, and more preferably between 3.1 and 6.8 wt. %.
[0016] In one embodiment, the composition and weight percentage of the soluble foam aluminum alloy are as follows: Mg content is 3.0-7.0wt.%; Cu content is 0.7-4.0wt.%; Zr content is 0.1-0.5wt.%; In content is 0.2-2.0wt.%; Ga content is 1.0-4.0wt.%; Sn content is 0.2-1.2wt.%; Ti: 0.05-1.0wt.%; and the balance is Al.
[0017] In one embodiment, the composition and weight percentage of the soluble foam aluminum alloy are: Mg content is 3.5-7.0wt.%; Cu content is 1.2-2.0wt.%; Zr content is 0.2-0.8wt.%; In content is 1.0-2.0wt.%; Ga content is 2.0-2.5wt.%; Sn content is 0.3-1.2wt.%; Ti content is 0.05-1.0wt.%; and the balance is Al.
[0018] In one embodiment, the soluble aluminum foam alloy has a compressive strength of not less than 67 MPa when the porosity is 60%-70%; and a corrosion rate of 78-145 mg / (h·cm 2 ), density is 0.9-1.1g / cm 3 .
[0019] The technical solution of the present invention also proposes a method for preparing the above-mentioned soluble foam aluminum alloy, characterized in that the method comprises the following steps:
[0020] (1) According to the weight ratio of Mg: 3.0-9.0wt.%; Cu: 0.5-5.0wt.%; Zr: 0.05-1.0wt.%; In: 0.05-3wt.%; Ga: 0.5-5wt.%; Sn: 0.05-1.5wt.%; the balance is Al. Add Al, Mg, Cu, Zr (zirconium), Ga (gallium), In (indium), Sn (tin) and smelt at 720-770℃; according to the difficulty of burning, first add Al to the furnace, then add Cu and Zr elements, then add Ga and In, and finally add Mg and Sn;
[0021] (2) adding a special refining agent for aluminum casting to the melt, stirring, evenly sprinkling an aluminum sodium-free slag remover on the surface of the melt, adding a titanium boron refiner after removing impurities, stirring evenly, and casting at 720-760° C. to obtain an ingot;
[0022] (3) One-step foaming: remelting the ingot that meets the requirements at 650-740°C, and after the ingot is melted and cooled to 620-680°C, adding viscosity enhancer particles, and stirring the melt for 6-15 minutes; adding a metal foaming agent, stirring for 50-320 seconds; and then cooling to obtain a soluble foam aluminum alloy billet;
[0023] (4) Two-step foaming: Place a certain mass of soluble foam aluminum alloy billet into a spherical, cylindrical, or special-shaped mold, and quickly place it in a 720-800°C heating furnace to heat it so that the billet in the mold is filled.
[0024] According to one aspect of the present invention, the method further comprises step (5): after the blank is completely filled, the mold is taken out as a whole and cooled, and after the mold is removed from the mold at room temperature, a soluble foam aluminum alloy material that can be used for temporary plugging of oil and gas fracturing is obtained.
[0025] According to one aspect of the present invention, the soluble foam aluminum alloy blank obtained in step (3) is processed into a spherical, columnar, or irregular shape, or used alone as a temporary plugging agent for oil and gas fracturing.
[0026] The ingot casting in step (2) is required to meet the following requirements: compressive strength of 1329-1420 MPa, tensile strength of 120-240 MPa, elongation of 1-10%, corrosion rate of 70-150 mg / (h·cm 2 ).
[0027] In one implementation, in step (3), the amount of tackifier particles added is 0.8-2.5 wt.% of the weight of the soluble foam aluminum alloy, and the tackifier stirring speed is 400-600 rpm.
[0028] In one implementation, in step (3), the amount of metal foaming agent added is 1.0-4.5wt.% of the weight of the soluble foam aluminum alloy, the foaming stirring speed is 850-1250rpm, and the time is 50-320s, preferably 120-200s.
[0029] In one implementation, in step (1), Al, Mg, and Sn are added in the form of pure metals; Cu and Zr are added in the form of intermediate alloys; In and Ga are added in the form of pure metals; preferably, Cu and Zr are added in the form of intermediate alloys of Al-50Cu and Al-10Zr, respectively.
[0030] In one implementation, in step (1), In and Ga are added in the form of a master alloy.
[0031] Compared with the prior art, the present invention has the following advantages:
[0032] 1. Mg and Cu are introduced into the technical solution of the present invention, wherein Mg, Cu and Al form a large number of network precipitation phases in the pore wall matrix, which effectively strengthens the matrix and improves the strength of the soluble foam aluminum alloy;
[0033] 2. A trace amount of Zr element is introduced into the technical solution of the present invention, wherein the Zr element forms an Al3Zr dispersed phase with the Al matrix, refines the grain size, introduces dispersion strengthening, and improves the strength of the soluble foam aluminum alloy;
[0034] 3. The viscosity-enhancing process of the soluble foam aluminum alloy solves the problem of increased fluidity caused by the introduction of low-melting-point elements such as In, Ga, and Sn, and improves the stability of the foam;
[0035] 4. The soluble aluminum foam alloy prepared by the technical solution of the present invention can achieve the following technical indicators: when the porosity is 60%-70%, the compressive strength is not less than 67MPa; the corrosion rate in 1% KCl solution at 90°C is 78-140mg / (h·cm 2 ), can meet the requirements of temporary plugging of fracturing in oil and gas wells; the density can be adjusted to 0.9-1.1g / cm 3 Compared with traditional soluble aluminum alloys, its density is only about 1 / 3 of that of traditional soluble aluminum alloys, and it can flow into the gaps with the fracturing fluid, achieving a good temporary plugging effect.
[0036] 5. The soluble foam aluminum alloy mentioned in the present invention not only combines the high porosity and low density characteristics of foam aluminum alloy, achieving significant lightweight, but also has the controllable solubility performance of soluble aluminum alloy. This new material organically combines the outstanding characteristics and advantages of soluble aluminum alloy and foam aluminum alloy. The prepared soluble foam aluminum alloy temporary plugging material can dissolve by itself after completing specific tasks such as fracturing and plugging, without the need for additional operations such as drilling, thereby reducing environmental burden and subsequent processing costs. The soluble foam aluminum alloy temporary plugging agent prepared by the present invention shows obvious technical advantages and application prospects in unconventional oil and gas production fracturing operations. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 The dissolution state of a dissolvable aluminum alloy foam ball of the present invention in a 90°C 1% KCl solution at different times. AF is shown in the dissolution state of the soluble aluminum alloy foam ball in a 90°C 1% KCl solution on the first, second, third, fifth, seventh and ninth days, respectively. DETAILED DESCRIPTION
[0038] The reagents or raw materials used in the present invention can be obtained commercially. Unless otherwise specified, the reagents or raw materials used in the present invention are used in a conventional manner in the art or in accordance with the product instructions.
[0039] One aspect of the present invention relates to a soluble foam aluminum alloy, characterized in that the chemical composition and weight percentage of the soluble foam aluminum alloy are: Mg: 3.0~9.0wt.%; Cu: 0.5~5.0wt.%; Zr: 0.05~1.0wt.%; Ti: 1.0~2.0wt.%; In: 0.05~3wt.%; Ga: 0.5~5wt.%; Sn: 0.05~1.5wt.%; the balance is Al.
[0040] In one embodiment, the weight percentage of In+Ga+Sn in the soluble foamed aluminum alloy is between 1.4 and 7.0 wt. %, preferably between 2.7 and 6.8 wt. %, and more preferably between 3.1 and 6.8 wt. %.
[0041] It should be noted that in the present invention, the weight percentage of In+Ga+Sn is limited to between 1.4 and 7.0wt.%, mainly because when the weight percentage of In+Ga+Sn is too low, the effect of destroying the surface film during the dissolution process is weak and cannot achieve an effective dissolution effect; when the weight percentage of In+Ga+Sn is too high, the fluidity of the alloy is enhanced, which is not conducive to the subsequent aluminum alloy filling.
[0042] In one embodiment, the composition and weight percentage of the soluble foam aluminum alloy are: Mg: 3.20wt.%; Cu: 1.30wt.%; Zr: 0.12wt.%; In: 0.40wt.%; Ga: 1.90wt.%; Sn: 0.40wt.%; Ti: 1.5wt.%; the balance is Al.
[0043] In one embodiment, the composition and weight percentage of the soluble foam aluminum alloy are: Mg: 5.5wt.%; Cu: 4.0wt.%; Zr: 0.18wt.%; In: 0.8wt.%; Ga: 2.5wt.%; Sn: 0.8wt.%; Ti: 1.5wt.%; and the balance is Al.
[0044] In one embodiment, the composition and weight percentage of the soluble foam aluminum alloy are: Mg: 6.0wt.%; Cu: 2.0wt.%; Zr: 0.3wt.%; In: 0.60wt.%; Ga: 1.0wt.%; Sn: 0.30wt.%; Ti: 1.5wt.%; and the balance is Al.
[0045] In one embodiment, the composition and weight percentage of the soluble foam aluminum alloy are: Mg: 4.0wt.%; Cu: 1.5wt.%; Zr: 0.2wt.%; In: 1.0wt.%; Ga: 2.0wt.%; Sn: 0.3wt.%; Ti: 1.5wt.%; and the balance is Al.
[0046] In one embodiment, the composition and weight percentage of the soluble foam aluminum alloy are: Mg: 7.0wt.%; Cu: 1.5wt.%; Zr: 0.8wt.%; In: 2.0wt.%, Ga: 2.5wt.%, Sn: 1.2wt.%, Ti: 1.5wt.%; the balance is Al.
[0047] In one embodiment, the composition and weight percentage of the soluble foam aluminum alloy are: Mg: 3.5wt.%; Cu: 0.8wt.%; Zr: 0.15wt.%; In: 0.2wt.%; Ga: 1.0wt.%; Sn: 0.2wt.%; Ti: 1.0wt.%; and the balance is Al.
[0048] In one embodiment, the composition and weight percentage of the soluble foam aluminum alloy are: Mg: 4.0wt.%; Cu: 2.5wt.%; Zr: 0.5wt.%; In: 0.8wt.%; Ga: 2.0wt.%; Sn: 0.3wt.%; Ti: 1.0wt.%; and the balance is Al.
[0049] In one embodiment, the composition and weight percentage of the soluble foam aluminum alloy are: Mg: 3.0wt.%; Cu: 0.7wt.%; Zr: 0.1wt.%; In: 2.0wt.%; Ga: 4.0wt.%; Sn: 0.8wt.%; Ti: 1.0wt.%; and the balance is Al.
[0050] The technical solution of the present invention also proposes a method for preparing the above-mentioned soluble foam aluminum alloy, characterized in that the method comprises the following steps:
[0051] (1) According to the weight ratio of Mg: 3.0-9.0wt.%; Cu: 0.5-5.0wt.%; Zr: 0.05-1.0wt.%; In: 0.05-3wt.%; Ga: 0.5-5wt.%; Sn: 0.05-1.5wt.%; the balance is Al, Al, Mg, Cu, Zr, Ga, In, Sn are added, and smelting is carried out at 720-770℃, wherein Al is added to the furnace first, followed by Cu and Zr elements, then Ga and In, and finally Mg and Sn according to the difficulty of burning;
[0052] (2) adding a special refining agent for aluminum casting to the melt, stirring, evenly sprinkling an aluminum sodium-free slag remover on the surface of the melt, adding a titanium boron refiner after removing impurities, stirring evenly, and casting at 720-760° C. to obtain an ingot;
[0053] (3) One-step foaming: remelt the ingot that meets the performance requirements at 620-740°C, wait for the ingot to melt and cool down to 620-680°C, add viscosity enhancer particles, and stir the melt for 6-15 minutes; add a metal foaming agent and stir for 50-320 seconds; then cool to obtain a soluble foam aluminum alloy billet;
[0054] (4) Two-step foaming: Put a certain mass of soluble foam aluminum alloy blanks into spherical, cylindrical, or special-shaped molds, and quickly put them into a 720-800℃ heating furnace for heating to fill the blanks in the mold.
[0055] According to one aspect of the present invention, the method further comprises step (5) of taking out the entire mold and cooling it after the blank is completely filled, and after the mold is released at room temperature, a soluble foam aluminum alloy that can be used for temporary plugging of oil and gas fracturing is obtained.
[0056] According to one aspect of the present invention, the soluble foam aluminum alloy blank obtained in step (3) is processed into a spherical, columnar, or irregular shape, or used alone as a temporary plugging agent for oil and gas fracturing.
[0057] In order to ensure that the performance of the final foam aluminum alloy meets the standards, the performance of the ingot used must also be within a certain range. The ingot in step (2) is required to meet the following requirements: compressive strength of 1329-1420MPa, tensile strength of 120-240MPa, elongation of 1-10%, corrosion rate of 70-150mg / (h·cm in 1% KCl solution at 90°C) 2 ).
[0058] The weight of the tackifier particles added is 0.8-2.5wt.% of the weight of the soluble foam aluminum alloy, and the melt is stirred at a stirring speed of 350-750rpm for 6-15min. The weight of the metal foaming agent added is 1.0-4.5wt.% of the weight of the soluble foam aluminum alloy material, and then stirring is continued, the stirring paddle speed is 850-1250rpm, and the stirring time is 50-320s.
[0059] The special refining agent for aluminum casting smelting can be NaCl 45wt%, KCl 50wt% and CaF25wt%. The viscosity enhancer is calcium particles. The metal foaming agent is titanium hydride (TiH2).
[0060] Hereinafter, specific embodiments of the present invention will be described in detail with reference to the accompanying drawings.
[0061] Example 1
[0062] According to the alloy proportion of 3.2% Mg, 1.3% Cu, 0.12% Zr, 1.9% Ga, 0.4% In, 0.4% Sn, and the rest is Al, use a cutting machine to prepare the corresponding mass of alloy raw materials. When the temperature in the furnace reaches 720°C, put Al into the crucible in the furnace; after Al is completely melted, add the Al-50Cu and Al-10Zr intermediate alloys preheated in a muffle furnace at 200°C to the melt, and after the temperature in the furnace returns to 720°C, keep it warm for 15 minutes to ensure that the alloy is completely melted; then put the aluminum foil-wrapped Ga and In into the melt, and keep it warm for 15 minutes to ensure that the metal is completely melted; then adjust the furnace temperature to 720°C, put the aluminum foil-wrapped Mg and Sn into the melt, and quickly cover it with a graphite cup cover to prevent excessive oxygen from entering and causing burning of the alloy, and keep it warm for 15 minutes. Ensure that the metal is completely melted; then add a special refining agent for aluminum casting inside the melt, and quickly cover it with a graphite cup to promote the refining agent to fully react in the melt; after the temperature stabilizes, sprinkle the aluminum sodium-free slag agent evenly on the surface of the melt, and after the surface forms a shell, use a slag spoon to remove impurities on the surface of the melt; finally, add a refiner containing Ti and B elements to the melt, use a graphite rod to stir the melt evenly, and after the furnace temperature returns to 720℃, take out the melt for casting, and finally obtain an alloy ingot with a designed composition of Al-3.2Mg-1.3Cu-0.12Zr-1.9Ga-0.4In-0.4Sn. The ingot that meets the performance requirements is transferred to the foaming furnace for remelting, and the temperature is immediately lowered to 620℃ when the ingot begins to melt. Add a tackifier, the weight of the tackifier added is 1.5wt.% of the weight of the soluble foam aluminum alloy material, and stir the melt at a stirring speed of 550rpm for 10min. Add a metal foaming agent, the weight of which is 3.0wt.% of the weight of the soluble foam aluminum alloy material, and then continue stirring, the stirring paddle speed is 1050rpm, and the stirring time is 220s. Finally, water-cooling is performed to obtain a soluble foam aluminum alloy billet. The obtained soluble foam aluminum alloy billet is cut into specific sizes, the billet is placed in a spherical, cylindrical, or special-shaped metal mold, and quickly placed in a 750℃ heating furnace for heating, at which time the billet in the mold is filled; after the billet is fully filled, the mold is taken out as a whole and cooled, and after it is cooled to room temperature, a soluble foam aluminum alloy material with a composition of Al-3.2Mg-1.3Cu-0.12Zr-1.9Ga-0.4In-0.4Sn-1.5Ti that can be used for temporary plugging of oil and gas fracturing is obtained after demolding.
[0063] Example 2
[0064] According to the alloy proportion of 5.5% Mg, 4.0% Cu, 0.18% Zr, 2.5% Ga, 0.8% In, 0.8% Sn, and the rest is Al, use a cutting machine to prepare the corresponding mass of alloy raw materials. When the temperature in the furnace reaches 730°C, put Al into the crucible in the furnace; after Al is completely melted, add the Al-50Cu and Al-10Zr intermediate alloys preheated in a muffle furnace at 200°C to the melt, and after the temperature in the furnace returns to 730°C, keep it warm for 15 minutes to ensure that the alloy is completely melted; then put the aluminum foil-coated Ga and In into the melt, and keep it warm for 15 minutes to ensure that the metal is completely melted; then adjust the furnace temperature to 740°C, put the aluminum foil-coated Mg and Sn into the melt, and quickly cover it with a graphite cup cover to prevent excessive oxygen from entering and causing burning of the alloy, and keep it warm for 15 minutes , to ensure that the metal is completely melted; then add a special refining agent for aluminum casting inside the melt, and quickly cover it with a graphite cup to promote the refining agent to fully react in the melt; after the temperature stabilizes, sprinkle the aluminum sodium-free slag agent evenly on the surface of the melt, and after the surface forms a shell, use a slag spoon to remove impurities on the surface of the melt; finally, add a refiner containing Ti and B elements to the melt, use a graphite rod to stir the melt evenly, and after the furnace temperature returns to 730℃, take out the melt for casting, and finally obtain an alloy ingot with a designed composition of Al-5.5Mg-4Cu-0.18Zr-2.5Ga-0.8In-0.8Sn. The ingot that meets the performance requirements is transferred to the foaming furnace for remelting, and the temperature is immediately lowered to 660℃ when the ingot begins to melt. Add tackifier particles, the weight of which is 0.8wt.% of the weight of the soluble foam aluminum alloy material, and stir the melt at a stirring speed of 350rpm for 6min. Add a metal foaming agent, the weight of which is 1.0wt.% of the weight of the soluble foam aluminum alloy material, and then continue stirring, the stirring paddle speed is 850rpm, and the stirring time is 50s. Finally, water-cooling is performed to obtain a soluble foam aluminum alloy billet. The obtained soluble foam aluminum alloy billet is cut into specific sizes, the billet is placed in a spherical, cylindrical, or special-shaped metal mold, and quickly placed in a 730°C heating furnace for heating, at which time the billet in the mold is filled; after the billet is fully filled, the mold is taken out as a whole and cooled, and after it is cooled to room temperature, a soluble foam aluminum alloy material with a composition of Al-5.5Mg-4Cu-0.18Zr-2.5Ga-0.8In-0.8Sn-1.5Ti that can be used for temporary plugging of oil and gas fracturing is obtained after demolding.
[0065] Example 3
[0066] According to the alloy proportion of 6.0% Mg, 2.0% Cu, 0.3% Zr, 1.0% Ga, 0.6% In, 0.3% Sn, and the rest is Al, use a cutting machine to prepare the corresponding mass of alloy raw materials. When the temperature in the furnace reaches 760°C, put Al into the crucible in the furnace; after Al is completely melted, add the Al-50Cu and Al-10Zr intermediate alloys preheated in a muffle furnace at 200°C to the melt, and after the temperature in the furnace returns to 760°C, keep it warm for 13 minutes to ensure that the alloy is completely melted; then put the aluminum foil-coated Ga and In into the melt, and keep it warm for 10 minutes to ensure that the metal is completely melted; then adjust the furnace temperature to 720°C, put the aluminum foil-coated Mg and Sn into the melt, and quickly cover it with a graphite cup cover to prevent excessive oxygen from entering and causing burning of the alloy, and keep it warm for 15 minutes , to ensure that the metal is completely melted; then add a special refining agent for aluminum casting inside the melt, and quickly cover it with a graphite cup to promote the refining agent to fully react in the melt; after the temperature stabilizes, sprinkle the aluminum sodium-free slag agent evenly on the surface of the melt, and after the surface forms a shell, use a slag spoon to remove impurities on the surface of the melt; finally, add a refiner containing Ti and B elements to the melt, use a graphite rod to stir the melt evenly, and after the furnace temperature returns to 720℃, take out the melt for casting, and finally obtain an alloy ingot with a designed composition of Al-6.0Mg-2.0Cu-0.3Zr-1.0Ga-0.6In-0.3Sn. The ingot that meets the performance requirements is transferred to the foaming furnace for remelting, and the temperature is immediately lowered to 640℃ when the ingot begins to melt. Add tackifier particles, the weight of the tackifier particles added is 1.5wt.% of the weight of the soluble foam aluminum alloy material, and stir the melt at a stirring speed of 550rpm for 10min. Add a metal foaming agent, the weight of which is 3wt.% of the weight of the soluble foam aluminum alloy material, and then continue stirring, the stirring paddle speed is 1000rpm, and the stirring time is 220s. Finally, water-cooling is performed to obtain a soluble foam aluminum alloy billet. The obtained soluble foam aluminum alloy billet is cut into specific sizes, the billet is placed in a spherical, cylindrical, or special-shaped metal mold, and quickly placed in a 730°C heating furnace for heating, at which time the billet in the mold is filled; after the billet is fully filled, the mold is taken out as a whole and cooled, and after it is cooled to room temperature, a soluble foam aluminum alloy material with a composition of Al-6.0Mg-2.0Cu-0.3Zr-1.0Ga-0.6In-0.3Sn-1.5Ti that can be used for temporary plugging of oil and gas fracturing is obtained after demolding.
[0067] Example 4
[0068] According to the alloy proportion of 4.0% Mg, 1.5% Cu, 0.2% Zr, 2.0% Ga, 1% In, 0.3% Sn, and the rest is Al, use a cutting machine to prepare the corresponding mass of alloy raw materials. When the temperature in the furnace reaches 750℃, put Al into the crucible in the furnace; after Al is completely melted, add the Al-50Cu and Al-10Zr intermediate alloys preheated in a muffle furnace at 200℃ into the melt, and after the temperature in the furnace returns to 750℃, keep it warm for 15 minutes to ensure that the alloy is completely melted; then put the aluminum foil-wrapped Ga and In into the melt, and keep it warm for 15 minutes to ensure that the metal is completely melted; then adjust the furnace temperature to 730℃, put the aluminum foil-wrapped Mg and Sn into the melt, and quickly cover it with a graphite cup cover to prevent excessive oxygen from entering and causing burning of the alloy, and keep it warm for 15 minutes. minutes to ensure that the metal is completely melted; then add a special refining agent for cast aluminum smelting into the melt, and quickly cover it with a graphite cup cover to promote the refining agent to fully react in the melt; after the temperature stabilizes, evenly sprinkle the aluminum sodium-free slag remover on the surface of the melt, and after the surface forms a shell, use a slag remover to remove impurities on the surface of the melt; finally, add a refiner containing Ti and B elements to the melt, use a graphite rod to stir the melt evenly, and after the furnace temperature returns to 730°C, take out the melt for casting, and finally obtain an alloy ingot with a designed composition of Al-4.0Mg-1.5Cu-0.2Zr-2Ga-1In-0.3Sn. The ingot that meets the performance requirements is transferred to the foaming furnace for remelting, and the temperature is immediately reduced to 680°C when the ingot begins to melt. Add tackifier particles, the weight of the added tackifier particles is 1.5wt.% of the weight of the soluble foam aluminum alloy material, and stir the melt at a stirring speed of 550rpm for 10min. Add a metal foaming agent, the weight of which is 3wt.% of the weight of the soluble foam aluminum alloy material, and then continue stirring, the stirring paddle speed is 1050rpm, and the stirring time is 220s. Finally, water-cooling is performed to obtain a soluble foam aluminum alloy billet. The obtained soluble foam aluminum alloy billet is cut into specific sizes, the billet is placed in a spherical, cylindrical, or special-shaped metal mold, and quickly placed in a 750°C heating furnace for heating, at which time the billet in the mold is filled; after the billet is fully filled, the mold is taken out as a whole and cooled, and after it is cooled to room temperature, demolding is performed to obtain a soluble foam aluminum alloy material with a composition of Al-4.0Mg-1.5Cu-0.2Zr-2Ga-1In-0.3Sn-1.5Ti that can be used for temporary plugging of oil and gas fracturing.
[0069] Example 5
[0070] According to the alloy proportion of 7% Mg, 1.5% Cu, 0.8% Zr, 2.5% Ga, 2.0% In, 1.2% Sn, and the rest is Al, use a cutting machine to prepare the corresponding mass of alloy raw materials. When the temperature in the furnace reaches 760°C, put Al into the crucible in the furnace; after Al is completely melted, add the Al-50Cu and Al-10Zr intermediate alloys preheated in a muffle furnace at 200°C to the melt, and after the temperature in the furnace returns to 760°C, keep it warm for 15 minutes to ensure that the alloy is completely melted; then put the aluminum foil-wrapped Ga and In into the melt, and keep it warm for 15 minutes to ensure that the metal is completely melted; then adjust the furnace temperature to 730°C, put the aluminum foil-wrapped Mg and Sn into the melt, and quickly cover it with a graphite cup cover to prevent excessive oxygen from entering and causing burning of the alloy, and keep it warm for 15 minutes. minutes to ensure that the metal is completely melted; then add a special refining agent for cast aluminum smelting into the melt, and quickly cover it with a graphite cup cover to promote the refining agent to fully react in the melt; after the temperature stabilizes, sprinkle the aluminum sodium-free slag agent evenly on the surface of the melt, and after the surface forms a shell, use a slag spoon to remove impurities on the surface of the melt; finally, add a refiner containing Ti and B elements to the melt, use a graphite rod to stir the melt evenly, and after the furnace temperature returns to 730°C, take out the melt for casting, and finally obtain an alloy ingot with a designed composition of Al-7Mg-1.5Cu-0.8Zr-2.5Ga-2In-1.2Sn. The ingot that meets the performance requirements is transferred to the foaming furnace for remelting, and the temperature is immediately reduced to 670°C when the ingot begins to melt. Add tackifier particles, the weight of the added tackifier particles is 1.5wt.% of the weight of the soluble foam aluminum alloy material, and stir the melt at a stirring speed of 650rpm for 12min. Add a metal foaming agent, the weight of which is 3wt.% of the weight of the soluble foam aluminum alloy material, and then continue stirring, the stirring paddle speed is 1050rpm, and the stirring time is 220s. Finally, water-cooling is performed to obtain a soluble foam aluminum alloy billet. The obtained soluble foam aluminum alloy billet is cut into specific sizes, the billet is placed in a spherical, cylindrical, or special-shaped metal mold, and quickly placed in a 750°C heating furnace for heating, at which time the billet in the mold is filled; after the billet is completely filled, the mold is taken out as a whole and cooled, and after it is cooled to room temperature, demolding is performed to obtain a soluble foam aluminum alloy material with a composition of Al-7Mg-1.5Cu-0.8Zr-2.5Ga-2In-1.2Sn-1.5Ti that can be used for temporary plugging of oil and gas fracturing.
[0071] Example 6
[0072] According to the alloy proportion of 3.5% Mg, 0.8% Cu, 0.15% Zr, 1.0% Ga, 0.2% In, 0.2% Sn, and the rest is Al, use a cutting machine to prepare the corresponding mass of alloy raw materials. When the temperature in the furnace reaches 740°C, put Al into the crucible in the furnace; after Al is completely melted, add the Al-50Cu and Al-10Zr intermediate alloys preheated in a muffle furnace at 200°C to the melt, and after the temperature in the furnace returns to 740°C, keep it warm for 20 minutes to ensure that the alloy is completely melted; then put the aluminum foil-coated Ga and In into the melt, and keep it warm for 20 minutes to ensure that the metal is completely melted; then adjust the furnace temperature to 740°C, put the aluminum foil-coated Mg and Sn into the melt, and quickly cover it with a graphite cup cover to prevent excessive oxygen from entering and causing burning of the alloy, and keep it warm for 20 minutes. The metal is completely melted; then a special refining agent for aluminum casting is added to the melt, and a graphite cup is quickly used to cover it to promote the refining agent to fully react in the melt; after the temperature stabilizes, the aluminum sodium-free slag remover is evenly sprinkled on the surface of the melt, and after the surface forms a shell, the impurities on the surface of the melt are removed with a slag remover; finally, a refiner containing Ti and B elements is added to the melt, and the melt is stirred evenly with a graphite rod. After the furnace temperature returns to 730°C, the melt is taken out for casting, and finally an alloy ingot with a designed composition of Al-3.5Mg-0.8Cu-0.15Zr-1Ga-0.2In-0.2Sn-1.0Ti is obtained. The ingot that meets the performance requirements is transferred to the foaming furnace for remelting, and the temperature is immediately lowered to 680°C when the ingot begins to melt. Add tackifier particles, the weight of which is 1.5wt.% of the weight of the soluble foam aluminum alloy material, and stir the melt at a stirring speed of 550rpm for 10min. Add a metal foaming agent, the weight of which is 3wt.% of the weight of the soluble foam aluminum alloy material, and then continue stirring, the stirring paddle speed is 1050rpm, and the stirring time is 220s. Finally, water-cooling is performed to obtain a soluble foam aluminum alloy billet. The obtained soluble foam aluminum alloy billet is cut into specific sizes, and the billet is placed in a spherical, cylindrical, or special-shaped metal mold, and quickly placed in a 750°C heating furnace for heating. At this time, the billet in the mold is filled; after the billet is fully filled, the mold is taken out as a whole and cooled, and after it cools to room temperature, demolding is performed to obtain a soluble foam aluminum alloy material that can be used for temporary plugging of oil and gas fracturing.
[0073] Example 7
[0074] According to the alloy proportion of 4.0% Mg, 2.5% Cu, 0.5% Zr, 2.0% Ga, 0.8% In, 0.3% Sn, and the rest is Al, use a cutting machine to prepare the corresponding mass of alloy raw materials. When the temperature in the furnace reaches 770°C, put Al into the crucible in the furnace; after Al is completely melted, add the Al-50Cu and Al-10Zr intermediate alloys preheated in a muffle furnace at 200°C to the melt, and after the temperature in the furnace returns to 770°C, keep it warm for 15 minutes to ensure that the alloy is completely melted; then put the aluminum foil-coated Ga and In into the melt, and keep it warm for 15 minutes to ensure that the metal is completely melted; then adjust the furnace temperature to 750°C, put the aluminum foil-coated Mg and Sn into the melt, and quickly cover it with a graphite cup cover to prevent excessive oxygen from entering and causing burning of the alloy, and keep it warm for 15 minutes , to ensure that the metal is completely melted; then add a special refining agent for aluminum casting inside the melt, and quickly cover it with a graphite cup to promote the refining agent to fully react in the melt; after the temperature stabilizes, sprinkle the aluminum sodium-free slag agent evenly on the surface of the melt, and after the surface forms a shell, use a slag spoon to remove impurities on the surface of the melt; finally, add a refiner containing Ti and B elements to the melt, use a graphite rod to stir the melt evenly, and after the furnace temperature returns to 730℃, take out the melt for casting, and finally obtain an alloy ingot with a designed composition of Al-4.0Mg-2.5Cu-0.5Zr-2.0Ga-0.8In-0.3Sn. The ingot that meets the performance requirements is transferred to the foaming furnace for remelting, and the temperature is immediately lowered to 680℃ when the ingot begins to melt. Add tackifier particles, the weight of the tackifier particles added is 1.5wt.% of the weight of the soluble foam aluminum alloy material, and stir the melt at a stirring speed of 550rpm for 10min. Add a metal foaming agent, the weight of which is 3wt.% of the weight of the soluble foam aluminum alloy material, and then continue stirring, the stirring paddle speed is 1050rpm, and the stirring time is 220s. Finally, water cooling is performed to obtain a soluble foam aluminum alloy billet. The obtained soluble foam aluminum alloy billet is cut into specific sizes, the billet is placed in a spherical, cylindrical, or special-shaped metal mold, and quickly placed in a 750℃ heating furnace for heating, at which time the billet in the mold is filled; after the billet is fully filled, the mold is taken out as a whole and cooled, and after it is cooled to room temperature, a soluble foam aluminum alloy material with a composition of Al-4.0Mg-2.5Cu-0.5Zr-2.0Ga-0.8In-0.3Sn-1.0Ti that can be used for temporary plugging of oil and gas fracturing is obtained after demolding.
[0075] Example 8
[0076] According to the alloy proportion of 3.0% Mg, 0.7% Cu, 0.1% Zr, 4.0% Ga, 2.0% In, 0.8% Sn, and the rest is Al, use a cutting machine to prepare the corresponding mass of alloy raw materials. When the temperature in the furnace reaches 770°C, put Al into the crucible in the furnace; after Al is completely melted, add the Al-50Cu and Al-10Zr intermediate alloys preheated in a muffle furnace at 200°C to the melt, and after the temperature in the furnace returns to 770°C, keep it warm for 10 minutes to ensure that the alloy is completely melted; then put the aluminum foil-wrapped Ga and In into the melt, and keep it warm for 10 minutes to ensure that the metal is completely melted; then adjust the furnace temperature to 750°C, put the aluminum foil-wrapped Mg and Sn into the melt, and quickly cover it with a graphite cup cover to prevent excessive oxygen from entering and causing burning of the alloy, and keep it warm for 15 minutes. minutes to ensure that the metal is completely melted; then add a special refining agent for aluminum casting inside the melt, and quickly cover it with a graphite cup to promote the refining agent to fully react in the melt; after the temperature stabilizes, sprinkle the aluminum sodium-free slag agent evenly on the surface of the melt, and after the surface forms a shell, use a slag spoon to remove impurities on the surface of the melt; finally, add a refiner containing Ti and B elements to the melt, use a graphite rod to stir the melt evenly, and after the furnace temperature returns to 750℃, take out the melt for casting, and finally obtain an alloy ingot with a designed composition of Al-3.0Mg-0.7Cu-0.1Zr-4.0Ga-2In-0.8Sn. The ingot that meets the performance requirements is transferred to the foaming furnace for remelting, and the temperature is immediately lowered to 680℃ when the ingot begins to melt. Add tackifier particles, the weight of the tackifier particles added is 2.5wt.% of the weight of the soluble foam aluminum alloy material, and stir the melt at a stirring speed of 750rpm for 15min. Add a metal foaming agent, the weight of which is 4.5wt.% of the weight of the soluble foam aluminum alloy material, and then continue stirring, the stirring paddle speed is 1250rpm, and the stirring time is 320s. Finally, water cooling is performed to obtain a soluble foam aluminum alloy billet. The obtained soluble foam aluminum alloy billet is cut into specific sizes, the billet is placed in a spherical, cylindrical, or special-shaped metal mold, and quickly placed in a 730°C heating furnace for heating, at which time the billet in the mold is filled; after the billet is fully filled, the mold is taken out as a whole and cooled, and after it is cooled to room temperature, a soluble foam aluminum alloy material with a composition of Al-3.0Mg-0.7Cu-0.1Zr-4.0Ga-2In-0.8Sn-1.0Ti that can be used for temporary plugging of oil and gas fracturing is obtained after demolding.
[0077] Comparative Example 1
[0078] Except that the Mg content was designed to be 1.5 wt %, the rest was carried out according to the description in Example 5.
[0079] Comparative Example 2
[0080] Except that the Mg content was designed to be 1.0 wt %, the rest was carried out as described in Example 8.
[0081] Table 1. Compression and dissolution properties of dissolvable aluminum foam alloys
[0082] The soluble aluminum foam alloy can float in the KCl solution simulating the downhole conditions, so that it can be easily plugged with the fracturing fluid. The addition of In, Ga, and Sn elements promotes the dissolution of the aluminum foam alloy. The soluble aluminum foam alloy ball gradually shrinks in 1 to 7 days, and on the 9th day, the soluble aluminum foam alloy ball breaks (such as Figure 1 As shown), it is confirmed that the soluble foam aluminum alloy material created by the present invention can be dissolved after effectively completing the temporary plugging task.
[0083] The above embodiments are only preferred embodiments of the present invention and are not intended to limit the present invention. Any additions, equivalent substitutions or improvements made under the spirit and principles of the present invention are deemed to be within the patent protection scope of the present invention.
Claims
1. A dissolvable aluminum alloy foam, wherein: The chemical composition and weight percentage of the soluble foam aluminum alloy are: Mg: 3.0-9.0wt.%; Cu: 0.5-5.0wt.%; Zr: 0.05-1.0wt.%; In: 0.05~3wt.%; Ga: 0.5-5wt.%; Sn: 0.05~1.5wt.%, Ti: 1.00~2.0wt.%; the balance is Al.
2. The soluble foamed aluminum alloy according to claim 1, wherein: The chemical composition and weight percentage of the soluble foam aluminum alloy are: Mg: 3.0-7.0wt.%; Cu: 0.7-4.0wt.%; Zr: 0.1~0.5wt.%; In: 0.2~2.0wt.%; Ga: 1.0~4.0wt.%; Sn: 0.2~1.2wt.%; Ti: 1.00~2.0wt.%; the balance is Al. Preferably, the chemical composition and weight percentage of the soluble foamed aluminum alloy are: Mg: 3.5-7.0wt.%; Cu: 1.2-2.0wt.%; Zr: 0.2~0.8wt.%; In: 1.0~2.0wt.%; Ga: 2.0~2.5wt.%; Sn: 0.3~1.2wt.%; Ti: 1.00~2.0wt.%; the balance is Al.
3. The soluble foamed aluminum alloy according to claim 1 or 2, wherein: The weight percentage of In+Ga+Sn in the soluble foamed aluminum alloy is between 1.4 and 7.0 wt. %, preferably between 2.7 and 6.8 wt. %, and more preferably between 3.1 and 6.8 wt. %.
4. The soluble foamed aluminum alloy according to claim 1 or 2, wherein: When the porosity of the soluble foam aluminum alloy is 60%-70%, its compressive strength is not less than 67MPa; the corrosion rate in 1% KCl solution at 90°C is 7-145mg / (h·cm 2 ), density is 0.9-1.1g / cm 3 .
5. The soluble foamed aluminum alloy according to claim 1 or 2, characterized in that: The foam sphere has a dense aluminum alloy outer skin and disorderly distributed closed pores inside with a pore size range of 1-6mm.
6. A method for preparing a soluble foamed aluminum alloy, characterized in that: The method comprises the following steps: (1) According to the weight ratio, Mg: 3.0-9.0wt.%; Cu: 0.5-5.0wt.%; Zr: 0.05-1.0wt.%; In: 0.05-3wt.%; Ga: 0.5-5wt.%; Sn: 0.05-1.5wt.%, the balance is Al, add Al, Mg, Cu, Zr, Ga, In, Sn, and smelt at 720-770℃, wherein Al is added to the furnace first, followed by Cu and Zr elements, then Ga and In, and finally Mg and Sn according to the difficulty of burning; (2) adding a special refining agent for aluminum casting to the melt, stirring, and then evenly sprinkling an aluminum sodium-free slag remover on the surface of the melt, removing impurities, adding a titanium boron refiner, stirring evenly, and casting at 720-760° C. to obtain an ingot; (3) One-step foaming: remelting the ingot that meets the requirements at 620-740°C, and after the ingot is melted and cooled to 640-680°C, adding a viscosity enhancer, and stirring the melt for 6-15 minutes; adding a metal foaming agent, stirring for 50-320 seconds; and then cooling to obtain a soluble foam aluminum alloy billet; (4) Two-step foaming: a certain mass of soluble foam aluminum alloy blank is placed into a spherical, cylindrical, or special-shaped mold, and quickly placed in a 720-800°C heating furnace for heating to fill the blank in the mold.
7. The method according to claim 6, wherein: The method further comprises step (5): after the blank is completely filled, taking out the mold and cooling it, and after the temperature drops to room temperature and demoulding, a soluble foam aluminum alloy material is obtained; or The soluble foamed aluminum alloy blank obtained in step (3) is machined into a spherical, columnar, or irregular shape, or used alone as a temporary plugging agent for oil and gas fracturing.
8. The method according to claim 6, wherein: The ingot casting in step (2) is required to meet the following requirements: compressive strength of 1329-1420 MPa, tensile strength of 120-240 MPa, elongation of 1-10%, corrosion rate of 70-150 mg / (h·cm 2 ).
9. The method according to claim 6, wherein: In step (3), the amount of the viscosity enhancer added is 0.8-2.5wt.% of the weight of the soluble foam aluminum alloy, and the viscosity enhancing stirring speed is 400-600rpm; Preferably, in step (3), the amount of the metal foaming agent added is 1.0-4.5wt.% of the weight of the soluble foamed aluminum alloy, the foaming stirring speed is 850-1250rpm, and the time is 50-320s, preferably 120s-200s. Preferably, in step (1), Al, Mg and Sn are added in the form of pure metals; Cu and Zr are added in the form of intermediate alloys; In and Ga are added in the form of pure metals; more preferably, Cu and Zr are added in the form of intermediate alloys of Al-50Cu and Al-10Zr, respectively.
10. Use of the soluble foamed aluminum alloy material according to any one of claims 1 to 4 in preparing temporary plugging materials for oil and gas production fracturing.
Citation Information
Patent Citations
Methods of manufacturing degradable alloys and products made from degradable alloys
CN101560619A
A high-strength closed-cell foam aluminum alloy and its preparation method
CN110468313B
A high-temperature soluble aluminum alloy, its preparation method and applications
CN114717456B
High-elongation soluble aluminum alloy and preparation method and application thereof
CN116005046A
Cited By
High-temperature controllable dissolution rate aluminum alloy and preparation method thereof
CN120683397A